Enhancing Improving Environmental Performance and Quality in Distribution Management through Sustainability Accounting - Wulan Retnowati; Rismawati (INVENTORY: JURNAL AKUNTANSI, 2026)
This study investigates the application of sustainability accounting in distribution management as a means to enhance environmental performance and supply chain transparency. Data were collected through structured surveys and in-depth interviews involving sustainability managers, logistics officers, and supply chain analysts, employing a mixed-methods approach. The quantitative analysis reveals that carbon emission tracking (75% implementation rate; impact score 8.5/10), resource efficiency initiatives (65%; 7.5/10), and waste management practices (55%; 6.5/10) significantly contribute to improved environmental performance. Furthermore, qualitative findings, supported by industry-specific case studies, highlight challenges related to data collection complexity and underscore the necessity for standardized measurement frameworks. The results align with Stakeholder Theory and the Triple Bottom Line framework, emphasizing the importance of environmental accountability and innovation in sustainable practices. This study also offers practical implications by recommending the integration of sustainability accounting frameworks, such as the Global Reporting Initiative (GRI), into distribution systems to strengthen transparency and long-term business sustainability. Overall, these findings enrich the discourse on sustainable supply chains by providing actionable insights for balancing operational efficiency with environmental responsibility.